Standard Calibration Tool Lending System With Iot Integrated Fingerprint Identification At PT Sentral Tehnologi Managemen - Pratama, Bambang Surya; Wilyanti, Sinka; Dionova, Brainvendra Widi; Manfaluthy, Mauludi; Putri, Arisa Olivia; Pratama, Legenda Pramewono (Jurusan Teknik Elektro UIN Sunan Gunung Djati Bandung, 2025)
The Internet of Things (IoT) is a network of interconnected devices that enables these objects to collect and exchange data. IoT offers an efficient solution for various fields, including the database recording of borrowing and returning calibration standard measuring instruments. This research aims to design and implement an automated IoT-based borrowing and returning system to support database recording effectiveness. The focus of this research includes the design of the borrowing and returning system, the method of transmitting data to Google Sheets, and email notifications when borrowing or returning activities occur. The research methods include the design of hardware consisting of a fingerprint sensor, infrared sensor, ESP32 microcontroller, liquid crystal display (LCD), and 4x4 keypad, as well as database recording to Google Sheets utilizing Google Sheets scripts and email notifications via Simple Mail Transfer Protocol (SMTP) connection. The research results show that the system was successfully developed with a high success rate for personnel identification accuracy, reaching up to 92%, with an average identification time of 1.42 seconds. Additionally, the developed system proved to be an effective solution for replacing the manual borrowing system, based on a survey of laboratory personnel.